MEMBACA BANTEN DALAM MOTIF CERITA RAKYAT - Nurfaidah, Resti (BEBASAN Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Banten was well-known as a regionof  historical and literary treasures. These two anthologies of folklore: "Golden Chicken Legend and Other Stories" and "Legend of Keong Gondang" shown those two things. This paper was written to  prove the harmonious life of  Banten people who were able to combine the concepts of their ancestors and the Islamic religion. This research useda qualitative  method through descriptive analysis. The theoretical concept used in this research was Pan Kosicki’sframing, and  representation of Stuart Hall. The results shew that Banten strived to become a harmonious region by combining between previous ancestral with Islamic religious concepts. Banten residents did not only leave legendary figures who were considered to have extraordinary services in the development of the history of the region. In addition, Banten residents also did not deny the presence of animals and objects that were considered to have an important role in their lives.